Performing social change on the island of Ireland - Murphy, Ciara L., author.
1 online resource.
Keywords: "This book examines the relationship between moments of significant social change on the island of Ireland and performance practice during the twentieth and twenty-first centuries. It examines how moments of significant change influence not only the content of performance practice but also the form and function of theatre production and reception. This book investigates how the Troubles and subsequent Peace Process, Second-Wave Feminism, the Celtic Tiger and neoliberalism, social revolution and the COVID-19 pandemic impacts the form and function of performance practice across the island of Ireland. Although these forms of theatre and performance making refer to varied and distinct lineages of practice internationally, there are key parallels that compel a study of their inter-relationality in a specific Irish context This book explores how the performance of Ireland illuminates histories and stories that are on the margins, illuminating the lived realities of everyday life through the presentation of moments of violence, oppression, and trauma as something that is as important as the larger narratives often ascribed to nationhood. This book asks how performance practice engages with and informs moments of major social change on the island of Ireland through the distinct yet intersecting lenses of place, performance form, and social context over the course of almost a century of Irish theatre and performance practice. Ciara"--